Inanspruchnahme psychosozialer Hilfen bei jungen Erwachsenen mit suizidalem Erleben und Verhalten - Weiss, Maren; Hildebrand, Anja; Stemmler, Mark (Psychotherapie Psychosomatik Medizinische Psychologie, 2024)
The study explores the utilization of psychosocial support by young adults facing suicidal ideation or impulses, considering a comprehensive spectrum of psychosocial services. The study sheds light on help utilization and gaps in service use among different groups. The data is derived from the baseline assessment of the research project "Outcome Evaluation [U25]". The sample includes 888 young adults who reported suicidal thoughts and behaviors. Among the participants, 55 % accessed at least one psychosocial service. Medical/psychotherapy services were the most utilized (54 %), followed by professional counseling (34 %) and non-professional self-help services (22 %). Gender differences were observed, with males using help less frequently than females and individuals with diverse gender identities. Participants in relationships were less likely to seek help than singles. A migrant background showed no consistent impact on service utilization. Psychological distress and suicide literacy were associated with increased service utilization. Regression analysis revealed that gender and relationship status remained predictors of service utilization even when considering mental distress, suicidal thoughts and behaviors, and suicide literacy.
CRIS-Team Scopus Importer:2024-10-11
Keywords: suicidal thoughts and behaviors; suicide literacy; utilization of mental health services; young adults